Evaluation of Chondroprotective Activity of Channa striatus in Rabbit Osteoarthritis Model. (3rd July 2019) - Abdul Kadir, Azidah; Abdul Kadir, Arifah; Abd Hamid, Roslida; Mat Jais, Abdul Manan; Omar, Julia; Sadagatullah, Abdul Nawfar; Badrin, Salziyan; Win, Thin Thin; Sirajudeen, K. N. S.; Salleh, Annas
Abstract : Objectives . The objective of the study is to evaluate the chondroprotective activity of Channa striatus (Channa) and glucosamine sulphate (glucosamine) on histomorphometric examinations, serum biomarker, and inflammatory mediators in experimental osteoarthritis (OA) rabbit model. Design . Anterior cruciate ligament transection (ACLT) was performed to induce OA in thirty-three male New Zealand white rabbits and were randomly divided into three groups: Channa, glucosamine, and control group. The control group received drinking water and the Channa and glucosamine groups were orally administered with 51.4 mg/kg of Channa extract and 77.5 mg/kg of glucosamine sulphate in drinking water, respectively, for eight weeks and then sacrificed. The articular cartilage was evaluated macroscopically and histologically using semiquantitative and quantitative methods. Serum cartilage oligomeric matric protein (COMP), cyclooxygenase 2 (COX-2) enzyme, and prostaglandin E2 (PGE2 ) were also determined. Results . Macroscopic analysis revealed that Channa group have a significantly lower severity grade of total macroscopic score compared to the control (p < 0.001) and glucosamine (p < 0.05) groups. Semiquantitative histology scoring showed that both Channa and glucosamine groups had lower severity grading of total histology score compared to the control group (p < 0.001). In comparison with the control, Channa group had lower histopathological changes in three compartments of the joint compared to glucosamine group which had lower histological scoring in two compartments only. The cartilage thickness, area, and roughness of both Channa (p < 0.05) and glucosamine (p < 0.05) groups were superior compared to the control group. However, the Channa group demonstrated significantly less cartilage roughness compared to the glucosamine group (p < 0.05). Serum COMP levels were lower in both Channa (p < 0.05) and glucosamine (p < 0.05) groups compared to the control group. Conclusion . Both oral administration of Channa extract and glucosamine exhibited chondroprotective action on an ACLT OA-induced rabbit model. However, Channa was superior to glucosamine in maintaining the structure of the cartilage.